2015
DOI: 10.4102/phcfm.v7i1.847
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of hypertension amongst adults in a rural community of Limpopo Province, South Africa

Abstract: BackgroundHypertension is problem already faced by urban populations of South Africa, but little is known about its prevalence and risk factors in rural areas.AimTo assess the prevalence of and risk factors associated with hypertension amongst adults in a rural community in South Africa.SettingDikgale Health and Demographic Surveillance Site, Limpopo Province, South Africa.MethodsA community-based cross-sectional survey was carried out at this site where individuals aged 15 years and older were screened using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
46
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 44 publications
14
46
1
Order By: Relevance
“…Hypertension remains the most common life-threatening risk factor for cardiovascular disease in developing countries [17]. As many as 88.4% of our subjects were hypertensive, which is similar to other independent local studies.…”
Section: Discussionsupporting
confidence: 90%
“…Hypertension remains the most common life-threatening risk factor for cardiovascular disease in developing countries [17]. As many as 88.4% of our subjects were hypertensive, which is similar to other independent local studies.…”
Section: Discussionsupporting
confidence: 90%
“…More than one third of the world adult populations suffer from HBP [3]. Sub-Saharan Africa is the region with the highest prevalence [3], ranging from 18% to 50% among adults [1] [4] [5] [6] [7]. The factors associated with HBP vary according to the epidemiological studies [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan Africa is the region with the highest prevalence [3], ranging from 18% to 50% among adults [1] [4] [5] [6] [7]. The factors associated with HBP vary according to the epidemiological studies [5] [6] [7]. High-income countries have begun to reduce the prevalence of HBP in their populations through collective prevention measures and the provision of widely accessible diagnosis and treatment services.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of inadequate management and control measures, the prevalence of hypertension in some African countries has increased significantly to more than 30% [7][8][9]. These high prevalence figures have been strongly linked with changes in individual and societal factors such as rapid urbanization, rising levels of obesity, increase in tobacco use, excessive alcohol consumption, reduced physical activity, and adoption of "Western" diets that are high in salt, refined sugar, and unhealthy fats and oils [10][11][12] Journal of Biomedical Education presented on the modifiable risk factors for hypertension revealed that a high intake of sodium is common in most African countries where salt is used to preserve food or to make it tastier [13].…”
Section: Introductionmentioning
confidence: 99%